Marjolin ulcer: the importance of early diagnosis and excision - Nathália Nunes Rodovalho; Larissa Rocha Alípio Duarte; Isadora Senna Guimarães; Ingrid Hovsepian de Souza; Luana Oliveira Magalhães; Manoel Pereira da Silva (Revista Brasileira de Cirurgia Plástica)
Introduction: Marjolin’s ulcer is a rare disease characterized by the malignancy of chronic wounds that present healing disorders, often due to chronic irritation and repetitive trauma in this area. The diagnosis is made mainly through clinical history and histopathological examination. The differential diagnoses of other diseases that course with ulcers must always be researched and ruled out. Method: The present work presents a bibliographic review to elucidate the subject’s relevance for medical students, physicians and nurses, to assist in early diagnosis. Results: Nine observational studies were selected to compose the discussion. Conclusion: The most effective treatment for this condition is surgery, and lymph node dissection is suggested in some cases. Chemotherapy has not shown satisfactory results, while radiotherapy is used in selected cases. Given the rapid evolution, tissue damage, and worse prognosis, diagnosis, and excision should be performed early for a better clinical outcome.